Quality, composition and production process of virgin olive oils - Lercker, G.; Bendini, A.; Cerretani, L. (Progress in Nutrition, 2007)
The olives are the raw material for olive oil production. The olive oil is a typical product of Mediterranean area and it is one of the basic component of the famous “Mediterranean diet”. It’s well-known that, in relation to the production of olives, every cultivar has its own peculiarity. Moreover, the characteristics of a same cultivar, are strongly influenced by agricultural methods and seasonal trend. Recently, several studies proved that the choice of the optimal maturation of the olives for the collection, play a role of primary importance. Instead, the influence of the storage of the olives before the production process, and the parameters that can negatively affect the final product, are well-known from long time. The presence of a small amount of micro-emulsified water in the filtered and very clear olive oils, recently discovered, brought new inputs for the interpretation of several behaviours that seemed contradictory in the past.